Dinamika Ekonomi Pembangunan Indonesia: Mengungkap Faktor-Faktor Kualitatif yang Mendorong Pertumbuhan - Irma Juliana; Nindi Laili Safitri; Wulan Fadillah (Universitas Katolik Widya Karya Malang, 2023)
This research aims to uncover the role of qualitative factors in driving the economic growth of Indonesia. The factors examined include community empowerment, business development, and the role of the manufacturing sector. Based on literature analysis, previous research, and relevant journals, the findings indicate that these factors have a significant influence in promoting inclusive, sustainable, and positively impactful economic growth for the society. Community empowerment through business development has been proven to enhance income, create job opportunities, and strengthen local-level economic growth. Research also indicates that the manufacturing sector plays a crucial role in generating value-added, absorbing workforce, driving innovation, and developing related sectors.